2012
DOI: 10.1111/j.1463-1318.2011.02810.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic restorative proctocolectomy: safety and critical level of the ileal pouch anal anastomosis

Abstract: In laparoscopic-assisted RPC a limited Pfannenstiel incision allows safe construction of the IPAA at an appropriate level. Laparoscopic RPC is safe and the emerging long-term follow-up data show the benefit of this approach, with very low rates of small bowel obstruction and incisional hernia formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Our finding that MIS-IPAA is safe and feasible and associated with short-term patient benefits is consistent with what has been reported by others. The conversion rate of 8 % seen in our series falls within the observed range of 1.4-13 % across other studies [18][19][20][21][22][23]. Mortality, postoperative complications and length of hospital stay reported in other series are also similar to those in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Our finding that MIS-IPAA is safe and feasible and associated with short-term patient benefits is consistent with what has been reported by others. The conversion rate of 8 % seen in our series falls within the observed range of 1.4-13 % across other studies [18][19][20][21][22][23]. Mortality, postoperative complications and length of hospital stay reported in other series are also similar to those in our study.…”
Section: Discussionsupporting
confidence: 87%
“…it is likely that the laparoscopic approach benefits patients in many important medium-and longterm aspects, eg, in terms of lower morbidity and faster recovery following the subsequent restoration of bowel continuity, 32 in addition to increased fecundity 6,7 and presumably a lower risk of incisional hernias. 33 although the power of this study predominantly lies in the considerable volume of Ral-iPaa procedures, there are several limitations, the most important of which is the observational single-center design, which imposes restrictions to the transferability of our results. furthermore, the overall economic feasibility of Ral was not determined, because we did not compare the costs of the 2 procedures.…”
Section: Discussionmentioning
confidence: 81%
“…30,34 in addition, at least 3 different studies have concurrently found that laparoscopic iPaa is associated with decreased rates of adhesions, possibly because of decreased small-bowel manipulation and incision length, 11-13 2 of which evaluated patients undergoing laparoscopic rectal dissection. 30,34 in addition, at least 3 different studies have concurrently found that laparoscopic iPaa is associated with decreased rates of adhesions, possibly because of decreased small-bowel manipulation and incision length, 11-13 2 of which evaluated patients undergoing laparoscopic rectal dissection.…”
Section: Discussionmentioning
confidence: 99%